Systematic review and network meta-analysis of the efficacy and safety of glycopyrrolate/formoterol fumarate metered dose inhaler in comparison with other long-acting muscarinic antagonist/long-acting β2-agonist fixed-dose combinations in COPD. (December 2019) - Siddiqui, Mohd Kashif; Shukla, Pragya; Jenkins, Martin; Ouwens, Mario; Guranlioglu, Deniz; Darken, Patrick; Biswas, Mousumi
Background: Dual bronchodilation with a long-acting muscarinic antagonist (LAMA)/long-acting β2 -agonist (LABA) fixed-dose combination (FDC) is an established treatment strategy for chronic obstructive pulmonary disease (COPD). The relative efficacy and safety of glycopyrrolate/formoterol fumarate metered dose inhaler (GFF MDI 18/9.6 μg) in patients with moderate-to-very severe COPD, compared with other licensed LAMA/LABA FDCs, was investigated using an integrated Bayesian network meta-analysis (NMA). Methods: A systematic literature review and subsequent screening process identified randomized controlled trials of ⩾10 weeks' duration that enrolled patients aged ⩾40 years with moderate-to-very severe COPD and included at least one LAMA/LABA FDC or open LAMA + LABA treatment arm. NMAs were conducted for outcomes including change from baseline in forced expiratory volume in 1 s (FEV1 ), St George's Respiratory Questionnaire (SGRQ), and transition dyspnea index (TDI) parameters, annualized rate of exacerbations, use of rescue medication, adverse events, and all-cause withdrawals. Meta-regression and sensitivity analyses accounted for heterogeneity across studies. Results: In total, 29 studies including 34, 617 patients contributed to the NMA for efficacy or safety outcomes at week 24 or exacerbations. For all LAMA/LABA FDCs with data available, significantly greater improvements in FEV1 [trough, peak, and area under the curve (AUC)0–4 ], SGRQ total score and TDI focal score at week 24, and annualized rate of moderate-to-severe exacerbations, were observed versus placebo. Where indirect comparisons were possible, differences between GFF MDI and other LAMA/LABA FDCs were small relative to established margins of clinical relevance, and not statistically significant. The safety and tolerability profile of GFF MDI was consistent with other LAMA/LABA FDCs and placebo. The results of the meta-regression were generally similar to the base case. Conclusions: GFF MDI demonstrated comparable efficacy and safety outcomes to other LAMA/LABA FDCs. Personalization of treatment choice within the class on the basis of other factors such as patient preference may be appropriate.